Theory of Islamic Entrepreneurship Management, Islamic Cooperatives, and Islamic SMEs at National and International Levels - S, Sugiharto; Fitri, Ummi Hannif; N, Nakamilo; Mahmud, Amir; Nuraini, Dinda; Sangputri, Dresnalaya; Fahmi, Khairul (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This article analyzes management theories within the sectors of entrepreneurship, cooperatives, and MSMEs through an Islamic economic perspective on both national and international scales. In Islam, entrepreneurship is defined as an innovative and risk-taking activity that must be grounded in the principles of Tawhid (oneness of God), justice, and Sharia ethics. The study highlights Islamic cooperatives as a representation of a people-based economy that prioritizes the spirit of ta’awun (mutual assistance) and profit-sharing systems, with significant developments observed in Indonesia, Malaysia, and Turkey. Meanwhile, MSMEs are positioned as a vital pillar for the growth of the halal economy and job creation. Overall, the integration of Islamic values across these three sectors shifts the business orientation from mere profit-seeking toward the attainment of maslahah (public interest) and long-term sustainability.